Studi etnoveteriner tumbuhan obat mastitis sapi perah oleh masyarakat Kecamatan Sendang, Kabupaten Tulungagung - Niken Ariningtyas; Eko Budi Minarno; Eni Setyowati (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2026)
Mastitis is a major disease in dairy cattle that significantly affects the quantity and quality of milk production. The community of Sendang District, Tulungagung Regency, whose livelihoods are predominantly based on farming and dairy cattle husbandry, possesses traditional knowledge of the use of medicinal plants for mastitis prevention and treatment. This study aimed to investigate the use of medicinal plants for mastitis in a local community. This study employed a descriptive exploratory method using survey and interview approaches conducted in six villages in the Sendang District: Geger, Kedoyo, Krosok, Nglurup, Nyawangan, and Sendang. The research subjects were community members from these villages who had knowledge of and utilized medicinal plants for mastitis treatment, selected through a purposive sampling method. The ethnoveterinary results revealed that four species of medicinal plants were used for the prevention and treatment of mastitis in dairy cattle: turmeric (Curcuma longa), betel leaf (Piper betle), moringa (Moringa oleifera), and papaya (Carica papaya), with turmeric being the most frequently used (32.14%). In conclusion, local communities still utilize a variety of medicinal plants, particularly leaves through traditional processing methods such as pounding, boiling, direct feeding, and grating. These practices are scientifically supported by the presence of bioactive compounds with antibacterial, anti-inflammatory, antioxidant, and immunomodulatory properties, offering a natural and sustainable alternative for the management of bovine mastitis.